Technical Analysis of Stock Prices Using Japanese Candlestick Method - Haider Abbas abdullah Aljanabi (Indonesian Journal of Law and Economics Review, 2026)
General Background: Technical analysis provides investors with systematic methodologies for understanding financial market dynamics through chart-based price movement examination. Specific Background: The Japanese candlestick method, originating from 17th century rice trading in Japan, visualizes market psychology through four-coordinate price data representing opening, closing, highest, and lowest values within defined timeframes. Knowledge Gap: Practical application and reliability validation of candlestick patterns in predicting stock price movements across varying market conditions remain insufficiently explored. Aims: This analytical research evaluates Japanese candlestick methodology effectiveness in technical analysis for stock pricing accuracy, examining single and multiple candle patterns to identify trends and reversals. Results: Candlestick patterns demonstrate 79.4% accuracy in predicting price directions, though requiring specialized expertise for proper implementation. Novelty: This study systematically examines pattern effectiveness integrating volume analysis and market contextual factors. Implications: Enhanced investor education through specialized training programs is essential for effectively leveraging Japanese candlestick analysis to optimize stock market investment returns.Keywords : Technical Analysis, Japanese Candlestick, Stock Price Prediction, Candlestick Patterns, Financial Market TrendsHighlight : Candlestick patterns achieve 79.4% accuracy in predicting stock price direction movements. Method demands specialized expertise due to complexity requiring extreme caution in application. Reversal patterns combined with volume analysis provide optimal trading entry-exit points.